1997
DOI: 10.1152/ajprenal.1997.272.4.f451
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and developmentally regulated expression of murine polycystin

Abstract: PKD1, the gene that is mutated in approximately 85% of autosomal dominant polycystic kidney disease (ADPKD) cases in humans, has recently been identified (Eur. PKD Consortium. Cell 77: 881-894, 1994; also, erratum in Cell 78: 1994). The longest open-reading frame of PKD1 encodes polycystin, a novel approximately 460-kDa protein that contains a series of NH2-terminal adhesive domains (J. Hughes, C. J. Ward, B. Peral, R. Aspinwall, K. Clark, J. San Millan, V. Gamble, and P. C. Harris. Nat. Genet. 10: 151-160, 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
99
1
3

Year Published

1999
1999
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(110 citation statements)
references
References 21 publications
7
99
1
3
Order By: Relevance
“…It is known that Pkd1 is also expressed in pancreatic ducts, hepatic bile ducts and Bowman's capsule, and thus coincides with the origin of the cysts as well. 5,35,36 These cysts can be found in ADPKD patients as well. Our data indicate that the SM22 promoter fragment that regulates the expression of Cre is not exclusively expressed in vascular SMCs.…”
Section: Discussionmentioning
confidence: 95%
“…It is known that Pkd1 is also expressed in pancreatic ducts, hepatic bile ducts and Bowman's capsule, and thus coincides with the origin of the cysts as well. 5,35,36 These cysts can be found in ADPKD patients as well. Our data indicate that the SM22 promoter fragment that regulates the expression of Cre is not exclusively expressed in vascular SMCs.…”
Section: Discussionmentioning
confidence: 95%
“…This may be a result of the age of mice we analyzed and a tightly regulated entry of PC1 and PC2 to cilia by proteins such as Nek8. It is known that PC1 expression is developmentally regulated, its expression level significantly decreases in wild-type mouse kidney after birth, 32 and it is barely detectable by immunofluorescence in the adult kidney, although it was easily detected in the fetal kidney. 14,32 Because we did observe very clear ciliary PC1 and PC2 expression in cultured cells with the same antibody, 17,20 we cannot exclude the possibility that the amount of ciliary PC1 and PC2 in the wild-type kidney is below the limit of immunohistochemical detection.…”
Section: (Yl and Jz Unpublished Observations)mentioning
confidence: 99%
“…This may be due to variations in the temporal and spatial expression pattern for polycystin-1 between species confounded by changing cellular localizations during development (63,64). This is further complicated by individual studies using different antibodies to various regions of polycystin-1, introducing an uncertainty in the detection of full-length polycystin-1, and detection of protein products from homologous genes.…”
Section: Tissue Distributionmentioning
confidence: 99%
“…However, murine polycystin-1 localization studies have also demonstrated low levels of polycystin-1 at the uteric bud (64) along with no detectable PKD1 mRNA in the uteric bud of human embryos at 10 weeks, challenging the role of polycystin-1 in nephrogenic induction (65). Maturing cortical tubules and collecting ducts also express polycystin-1 at moderately high levels during embryonic development (7,64,66). Other localization studies show evidence for polycystin-1 expression within the glomerulus (66); either at the glomerular tuft or parietal cells of Bowman's capsule (7,67).…”
Section: Tissue Distributionmentioning
confidence: 99%